THE PRINCIPALS’ LEADERSHIP IN MANAGING JOB DESCRIPTION AT MAN 2 BANDA ACEH - Mizal, Basidin; Hasnaini, Hasnaini; Tathahira, Tathahira (Jurnal As-Salam, 2022)
The leadership of the madrasa principal substantially plays a significant role in promoting the quality of an educational institution. Implementing the job description in specific departments should be carefully applied and fulfill the applied procedures. The objective of this study was to find out the process of job description application conducted by the principal of MAN 2 Banda Aceh. This study is categorized as qualitative research, employing observation, interview, and documentation as data collection techniques. The data were analyzed through several steps: data reduction, data display, and conclusion. The findings of this study indicated that the principal of MAN 2 Banda Aceh has administratively implemented job description management based on the existing regulation. Managerially, the principal held specific tests for the employees (teachers and staff) assigning the job description. In addition, conditions and criteria were established in deciding the job description, namely formation request, educational background, working experience, physical and mental health, age, social relationship, and so on. The principal of MAN 2 Banda Aceh faced some obstacles in placing the job description encompassing internal and external factors, namely the mindset and culture-set of employees. At the same time, externally, they were influenced by the complex skill and possible personal and political interests of personnel.